Characterization and flocculation evaluation of a new organic–inorganic hybrid polymer flocculant (PAC‐AM‐DMC). Issue 47 (10th July 2021) - Chen, Meijun; Zou, Changjun; Tang, Wenyue; Huang, Yushuang; Sun, Huahong
Abstract: A novel organic–inorganic hybrid flocculant PAC‐AM‐DMC is synthesized using potassium persulfate as an initiator, which was used in industrial wastewater treatment. Comparing with the traditional inorganic flocculant, this new flocculant has the advantage of low dosage and high efficiency. Simultaneously, it is less toxic and more environmentally friendly than the organic flocculant. The organic–inorganic hybrid flocculant PAC‐AM‐DMC demonstrates better flocculation than the commercial single type flocculant (PAC, PAM), and the effect is better than simply combining the two flocculants. It has potential for commercialization. When PAC:(AM + DMC) = 2:8, the initiator is 0.2 wt%, and the flocculant obtained by reacting at 50°C for 4 h has the best effect on sewage treatment. When the pH is 7, the treatment effect of PAC‐AM‐DMC is best with the dosage of 10 ppm. Correspondingly, the amount of flocculant is 10 mg/L, and the turbidity of simulated sewage is 172 nephelometric turbidity unit (NTU), which is over 98% of turbidity removal efficiency. In addition, the prepared hybrid flocculant is nearly non‐corrosive and posed little damage to the equipment. And the hybrid flocculant has excellent salt resistance. Abstract : Synthesis mechanism of flocculant.